Sino-Pakistani Sports and Cultural Cooperation under the ‘Belt and Road’ Initiative: Soft Connections and a Community with a Shared Future for Mankind - Xiaohui, Li; Hussain, Mahboob (sourcecoder, 2025)
This study explores China–Pakistan sports and cultural cooperation (1951–2021) within the Belt and Road Initiative (BRI), focusing on its role as a “soft connectivity” mechanism beyond economic infrastructure.Sports and culture function as non-linguistic channels that transcend linguistic, religious, and cultural boundaries. They provide cross-cultural adaptability, fostering mutual understanding, cultural identity, and national image within the “all-weather strategic partnership.”Using historical analysis, case studies, and interdisciplinary theory, the paper examines stages of exchange and their evolving functions.Findings reveal four stages of development: exploration, institutionalisation, diversification, and synergy. Exchanges have shifted from symbolic gestures to structured collaboration, creating new platforms for youth, education, and social integration. Challenges include weak institutionalisation, communication barriers, and limited evaluation mechanisms.Strengthening institutional frameworks, enhancing cross-cultural dialogue, and advancing Global South cooperation through sports and culture are recommended for sustaining long-term people-to-people connectivity.